RELATIONSHIP BETWEEN COMPETENCY OF EDUCATIONAL INSTITUTION ADMINISTRATORS AND ACADEMIC ADMINISTRATION OF SCHOOLS UNDER LAKSI DISTRICT OFFICE, BANGKOK - Sensarn , Artitapron; Rumakhom, Vassiga (Journal of Educational Review Faculty of Education in MCU, 2024)
This research aims to: 1) study the competency of school administrators under the jurisdiction of the Office of the Fourth Educational Area, Bangkok, 2) examine the academic management of schools under the jurisdiction of the Office of the Fourth Educational Area, Bangkok, and 3) investigate the relationship between the competency of school administrators and the academic management of schools under the jurisdiction of the Office of the Fourth Educational Area, Bangkok. The research utilized a descriptive research method with a sample group of 144 teachers in the academic year 2023. The research tools included questionnaires for data collection and basic statistical analysis methods such as frequency, percentage, mean, standard deviation, and Pearson correlation coefficient. The research findings indicate that school administrators of schools under the jurisdiction of the Office of the Fourth Educational Area, Bangkok, have the highest overall competency level. Similarly, the academic management of schools under this jurisdiction is also at the highest level. Furthermore, there is a significantly high positive correlation between the competency of school administrators and academic management in schools under the Office of the Fourth Educational Area, Bangkok.